Dataset for the role of sustained attention in memory formation of transgenic mice for Alzheimer׳s disease - Schöwe, Natalia Mendes (Data Brief, 2016)
Weekly submission of rats to active avoidance apparatus can be considered a neurostimulation strategy, once it can improve memory and can increase the density of receptors from different neurotransmitter systems in brain areas related to memory. These benefits were observed in rats chronically infused with amyloid-β peptide. In the present work it is presented that the same benefit for memory was observed in five months old transgenic mice for Alzheimer’s disease (TG-PDGFB-APP(Sw,Ind)). However, at this age, no change in density of nicotinic receptors was observed.